ZnO composite nanolayer with mobility edge quantization for multi-value logic transistors - Lynn Lee (Nature Portfolio, 2019)
Designing multi-value logic transistors with stable and reliable intermediate states remains a challenge. Here, the authors report the mobility edge quantization phenomenon via resonant hybridization of ZnO QDs embedded in amorphous ZnO domains to enable adjustable multi-value intermediate states.